2019
DOI: 10.1177/0143624419847621
|View full text |Cite
|
Sign up to set email alerts
|

The summer indoor temperatures of the English housing stock: Exploring the influence of dwelling and household characteristics

Abstract: As the high temperatures experienced during the summer of 2018 may become commonplace by 2050, adaptation to higher indoor temperatures while minimising the need for mechanical cooling is required. A thorough understanding of the factors that influence indoor temperatures can enable the design of healthier and safer dwellings under a warming climate. The aim of this paper is to provide further insight into the topic of indoor overheating through the analysis of the largest recent sample of English dwellings, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…These findings inferred that occupants lack awareness of how systems and passive cooling measures could significantly contribute to increased overheating levels indoors. Petrou, Mavrogianni and Symonds et al 46 showed that when the number of occupants was increased, the internal "overheating", "natural ventilation" " window opening" Natural ventilation "overheating", "vegetation" " green roof", "green wall" Vegetation "overheating", "solar shading" " fixed shading", "solar protection", "shutter" Solar shading "overheating", "thermal mass" " PCM", "heavyweight construction", "lightweight construction"…”
Section: Occupancymentioning
confidence: 97%
“…These findings inferred that occupants lack awareness of how systems and passive cooling measures could significantly contribute to increased overheating levels indoors. Petrou, Mavrogianni and Symonds et al 46 showed that when the number of occupants was increased, the internal "overheating", "natural ventilation" " window opening" Natural ventilation "overheating", "vegetation" " green roof", "green wall" Vegetation "overheating", "solar shading" " fixed shading", "solar protection", "shutter" Solar shading "overheating", "thermal mass" " PCM", "heavyweight construction", "lightweight construction"…”
Section: Occupancymentioning
confidence: 97%
“…The comparison of heat resilience for two buildings in two different countries-performed in this study-is motivated by the fact that the authors did not found any scientific literature comparing the heat resilience of apartment buildings in different countries. In the past, the scientific literature concerning overheating analysis in residential buildings was dominated by numerous investigations located in Great Britain [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. However, in the last years a significant increase in studies focussing overheating evaluations could be obtained all around the globe, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Previous field studies have, understandably given limited resources, focused on monitoring temperatures in only the living room and main bedroom (e.g. Beizaee et al 2013;Lomas & Kane 2013;Petrou et al 2019). Sometimes, information about sleep and heat is obtained from interviews and other social survey methods (e.g.…”
Section: Introductionmentioning
confidence: 99%